Magnetic Resonance Imaging Findings in Lumbosacral Spine among Young Arabic Patients with Back Pain - Mustafa, Wadyan (Khalij-Libya Journal of Dental and Medical Research, 2024)
Lower back pain is a significant health issue that affects approximately 80% of adults. Lumbar disc herniation is a common cause of this pain, and lumbosacral magnetic resonance imaging (MRI) is considered the gold standard for diagnosing disc abnormalities. Due to socioeconomic factors, there has been an increased interest in studying disc herniation among young individuals. This retrospective study involved 72 consecutive Arabic patients (34 females and 38 males) aged between 15 and 30 years, all presenting with lower back pain. The aim was to investigate the magnetic resonance imaging findings of the lumbosacral spine. Our study reveals a high prevalence of disc abnormalities in young patients, with approximately 40 individuals (55.6%) exhibiting varying degrees of disc prolapse and bulging. The older subgroup (ages 23-30) was more significantly affected, with no discernible sex predominance. The L4/L5 disc level was the most commonly involved (40%), and central disc prolapse was identified as the most frequent type, observed in 65% of cases. This study revealed a high prevalence of disc prolapse among individuals aged 15 to 30 years, which may be attributed to factors such as lifting heavy objects, obesity, and fluctuations in physical activity levels, both increased and decreased. الام أسفل الظهر هي مشكلة صحية كبيرة تؤثر على ما يقرب من 80٪ من البالغين. يعد الانزلاق الغضروفي القطني سببًا شائعًا لهذا الألم، ويعتبر التصوير بالرنين المغناطيسي القطني العجزي المعيار الذهبي لتشخيص تشوهات القرص. بسبب العوامل الاجتماعية والاقتصادية، كان هناك اهتمام متزايد بدراسة الانزلاق الغضروفي بين الأفراد الشباب. شملت هذه الدراسة الاسترجاعية 72 مريضًا عربيًا متتاليًا (34 أنثى و 38 ذكرًا) تتراوح أعمارهم بين 15 و 30 عامًا، وجميعهم يعانون من آلام أسفل الظهر. كان الهدف هو التحقيق في نتائج التصوير بالرنين المغناطيسي للعمود الفقري القطني العجزي. تكشف دراستنا عن انتشار مرتفع لتشوهات القرص بين المرضى الشباب، حيث أظهر ما يقرب من 40 فردًا (55.6٪) درجات متفاوتة من تدلي القرص وانتفاخه. كانت المجموعة الفرعية الأكبر سنًا (من سن 23 إلى 30 عامًا) أكثر تأثرًا بشكل ملحوظ، مع عدم وجود غلبة جنسية ملحوظة. كان مستوى القرص L4/L5 هو الأكثر تأثرًا (40٪)، وتم تحديد تدلي القرص المركزي باعتباره النوع الأكثر شيوعًا، حيث لوحظ في 65٪ من الحالات. كشفت هذه الدراسة عن انتشار مرتفع لتدلي القرص بين الأفراد الذين تتراوح أعمارهم بين 15 و 30 عامًا، والذي قد يعزى إلى عوامل مثل رفع الأشياء الثقيلة والسمنة وتقلبات مستويات النشاط البدني، سواء كانت متزايدة أو منخفضة